Ferroptosis in cancer: revealing the multifaceted functions of mitochondria - Xinyi Ding; Lei Cui; Yanjun Mi; Jiachun Hu; Zheyou Cai; Qing Tang; Linhao Yang; Zhuang Yang; Qingbing Wang; Hongsheng Li; Benxin Hou; Quentin Liu; et al. (Cellular and Molecular Life Sciences)
Abstract Ferroptosis is a programmed cell death characterized by iron-dependent lipid peroxidation, which is regulated by various cellular metabolic and signaling pathways. The main regulatory mechanisms of intracellular ferroptosis include the GSH-GPX4 pathway, the FSP1-CoQ10 pathway, the GCH1-BH4 pathway, and the DHODH-CoQH2 system. As the hub of iron metabolism and energy generation, mitochondria have been increasingly implicated in ferroptosis, underscoring their pivotal role in cellular processes. Ferroptosis is a significant mode of cell demise linked to cancer progression. It is expected to combat drug-resistant tumors by triggering iron-mediated cell death. This review delves into the intricate mechanisms governing intracellular ferroptosis, emphasizing the centrality of mitochondria in regulating this process within cancer cells. Furthermore, this review explores the potential and hurdles of targeting ferroptosis as a therapeutic avenue to overcome resistance to cancer treatment.